VALIDATING THE EVIDENCE OF VIOLENCE IN PARTNER RELATIONSHIPS WITH REGARD TO XHOSA AFRICAN WOMEN - Mesatywa, Nontando Jennifer (Social work, 2014)
This article reports on how African women understand the forms and meaning of violence in partner relationships. The findings suggest that many African women experience physical, emotional and economic abuse. Some of the reasons for abuse which emerged include a patriarchal system, alcohol abuse, infidelity and failure to support children financially. The influence of Xhosa African practices on violent partner relationships was explored. The study indicates a need for ethnically sensitive interdisciplinary programmes for social service practitioners, and an effective, accessible legal system for rural women to reduce incidences of abuse.